DOMESTIC VIOLENCE AGAINST WOMEN: EXPERIENCES OF PRIMARY HEALTH CARE PROFESSIONALS - Rodrigues, Paula Sales [UNESP]; Araujo, Laissa Figueredo; Vernasque, Juliana Ribeiro da Silva [UNESP]; de Souza, Aline Pereira [UNESP]; Alarcon, Miriam Fernanda Sanches; Higa, Elza de Fátima Ribeiro; Marin, Maria José Sanches [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: to analyze how Primary Health Care professionals experience domestic violence against women. Method: qualitative research, conducted from January to June 2023, through interviews with 20 Primary Health Care professionals, in a medium-sized municipality in the state of São Paulo, Brazil. The data obtained were interpreted using the Content Analysis Technique, thematic modality. Results: professionals emphasize the need for a sensitive approach and early identification, expressing feelings of perplexity and powerlessness during care. The impacts of violence are perceived by the victims, families, and society, causing physical, psychological, and social consequences. Challenges include lack of training, fear of reprisals, and lack of institutional support. The limitations faced by women in confronting violence are linked to lack of information, financial and emotional dependence, generating fear and insecurity. Conclusion: professionals experience the complexity of providing health care to women who are victims of domestic violence, and it is inferred that investments in professional training, institutional protection, and the creation of spaces that can support women are necessary to prevent re-victimization.
VIOLENCIA DOMÉSTICA CONTRA LAS MUJERES: EXPERIENCIA DE LOS PROFESIONALES DE LA ATENCIÓN PRIMARIA DE LA SALUD
VIOLÊNCIA DOMÉSTICA CONTRA AS MULHERES: VIVÊNCIAS DOS PROFISSIONAIS DA ATENÇÃO PRIMÁRIA A SAÚDE
Keywords: Domestic violence; Health staff; Nursing; Primary health care; Violence against women; Women